EVALUASI POTENSI RISIKO KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PROYEK PEMBANGUNAN PLTMGU LOMBOK (PEAKER) 130 – 150 MEGAWATT DENGAN METODE JOB SAFETY ANALYSIS (JSA) - LALU WIRAHMAN WIRADARMAN; TETI HANDAYANI; ZAEDAR GAZALBA; I WAYAN SUTEJA (GANEC SWARA, 2023)
The 130-150 Megawatt (Mw) Lombok PLTMGU (Peaker) Development Project is one of the PT PLN (Persero) projects undertaken by the PT Pembangunan Perumahan (Persero) tbk - Wartsila Consortium. In its implementation, it has a fairly high level of risk of work accidents. The purpose of this research is to understand the factors that have the highest risk of accidents based on the Job Safety Analysis (JSA) method. The data in this study were obtained by distributing questionnaires to parties involved in the implementation of the 130-150 Mw Lombok PLTMGU (Peaker) project. To determine risk classifications such as: Low, Medium, High and Very High a risk assessment is carried out based on the potential hazard obtained through a questionnaire test and the highest percentage is taken, the value obtained will be analyzed according to the standard guidelines of AZ/NZS 4360: 2004 using the JSA method (Job Safety Analysis). The results of the analysis with 28 stages of activity showed that the types of work with medium risk were piling, foundation hammering, painting and floor finishing, while for the highest level of risk were dismantling scaffolding, wall panel erection, intake head foundation erection, installation of intake head, pipe material transfer (ocean) and pipe installation (offshore).